2002
DOI: 10.1177/152660280200900617
|View full text |Cite
|
Sign up to set email alerts
|

Endograft Therapy for Diseases of the Descending Thoracic Aorta: Results in 43 High-Risk Patients

Abstract: Treatment of descending thoracic aortic diseases with an endovascular approach has acceptable early mortality and morbidity in high-risk patients. In selected cases, stent-grafts may afford the best therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 27 publications
(40 reference statements)
1
27
0
Order By: Relevance
“…[40][41][42] In the TAAA endograft series that used SFD prophylactically, the O/E ratio was 0.54; 39-41 the mean O/E ratio for series reporting open TAAA repair using only SFD without hypothermia and neurochemical protection was approximately 0.55. In endograft series that used no protective adjuncts, the O/E ratio was 1.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] In the TAAA endograft series that used SFD prophylactically, the O/E ratio was 0.54; 39-41 the mean O/E ratio for series reporting open TAAA repair using only SFD without hypothermia and neurochemical protection was approximately 0.55. In endograft series that used no protective adjuncts, the O/E ratio was 1.05.…”
Section: Discussionmentioning
confidence: 99%
“…In endograft series that used no protective adjuncts, the O/E ratio was 1.05. 35,36,[40][41][42] We recognize that most thoracic endovascular aortic repair (TEVAR) series have low-risk patients and those TEVAR series we included we modeled as thoracic aneurysms, which have a risk coefficient in the model of 0.01. The model assesses the risk of the population being studied whether it is high or low.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages reported in the literature range from 0% to 44%. [14][15][16] In this study population, the rate of primary leaks was 23%. An inlet less than 2 cm from the left subclavian artery and located in the lesser curvature of the aortic arch is one of the factors predisposing to stent kinking and leaks during control angiography, as well as previous aortic surgical or endovascular manipulation.…”
Section: Discussionmentioning
confidence: 78%
“…The period of spontaneous resolution ranges from one week to eight months. In case of persistence of such leakage, corrective therapeutic interventions must be performed (11) . In the population with type I leakage, the authors found five patients in G1 and two in G2 with low-volume leakages at arteriography, which spontaneously resolved between the third and sixth months of follow-up.…”
Section: (7)mentioning
confidence: 99%